2014
DOI: 10.1021/es500483w
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytic Membrane Extraction Enables Production of Fine Chemicals from Biorefinery Sidestreams

Abstract: Short-chain carboxylates such as acetate are easily produced through mixed culture fermentation of many biological waste streams, although routinely digested to biogas and combusted rather than harvested. We developed a pipeline to extract and upgrade short-chain carboxylates to esters via membrane electrolysis and biphasic esterification. Carboxylate-rich broths are electrolyzed in a cathodic chamber from which anions flux across an anion exchange membrane into an anodic chamber, resulting in a clean acid con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 28 publications
1
96
0
1
Order By: Relevance
“…Optimization of other parts of the electrochemical hardware such as the ion-exchange membrane and the current-collecting structure for MES processes are also ongoing (Varcoe et al, 2014). For example, it has been suggested that anion-exchange membranes can be exploited in the in situ selective extraction of acetate produced by MES at a lower energetic cost (Andersen et al, 2014). Furthermore, understanding in detail how electrons are transferred from the cathode to the microbial catalyst will help devise better-designed strategies to improve all aspects of MES.…”
Section: Resultsmentioning
confidence: 99%
“…Optimization of other parts of the electrochemical hardware such as the ion-exchange membrane and the current-collecting structure for MES processes are also ongoing (Varcoe et al, 2014). For example, it has been suggested that anion-exchange membranes can be exploited in the in situ selective extraction of acetate produced by MES at a lower energetic cost (Andersen et al, 2014). Furthermore, understanding in detail how electrons are transferred from the cathode to the microbial catalyst will help devise better-designed strategies to improve all aspects of MES.…”
Section: Resultsmentioning
confidence: 99%
“…One obvious approach to resolve this issue would be to concentrate acetic acid before lipid conversion. However, concentration of dilute acetic acid would introduce high costs at an industrial scale (3,19). Furthermore, the use of concentrated acetic acid in a fermentation process may result in significant carbon losses due to incomplete consumption by the cells and…”
mentioning
confidence: 99%
“…fermenters) [90]. Membrane Electrolysis (ME) was also showed successful for the extraction of carboxylates from cathode to anode compartment, combined with Biphasic Esterification (BE) for the production of fine chemicals [91]; similar concept could be coupled to microbial electrosynthesis of acetate from CO 2 .…”
Section: Microbial Electrosynthesis From Co2 To Organics-a Reviewmentioning
confidence: 99%
“…Membrane Electrolysis (ME) was also showed successful for the extraction of carboxylates from cathode to anode compartment, combined with Biphasic Esterification (BE) for the production of fine chemicals [91]. A similar concept could be coupled to microbial electrosynthesis of acetate with the recirculation of the acetate in a separate reactor where the esterification reaction takes place, as represented in Figure 53.…”
Section: Case Study Nº1: Co 2 Conversion To Acetate As End-productmentioning
confidence: 99%
See 1 more Smart Citation